Camrelizumab Combined With Gemcitabine and Albumin-Bound Paclitaxel for Neoadjuvant Therapy in the Treatment of Progressive Gallbladder Cancer: A Case Report - Wu, Jing; Wang, Zheng; Li, Jing; Peng, Xue-Hui; Tang, Yi-Chen; Huang, Xiao-Bing; He, Yong-Gang (Frontiers in Oncology, 2022)
The roles of immune checkpoint inhibitors in treating gallbladder cancer are still unclear and challenged by controversial findings.still under investigations and face many challenges. Research hasRecent research has shown that immune checkpoint inhibitors in combination with chemotherapy can may alleviate disease progression. CASE SUMMARY A 45-year-old female patient with gallbladder cancer accompanied by multiple abdominal lymph node metastasis was treated with camrelizumab combined with paclitaxel for injection (albumin-bound) and gemcitabine (AG) to downstage the tumor before a radical surgery could be performed. The postoperative quality of life was superior to the preoperative level”. CONCLUSION Camrelizumab plus AG offers a new therapeutic option for gallbladder cancer with multiple abdominal lymph node metastasis, which, however, warrants further validation in clinical trials.